Integration of Customary Marriage Law Into Positive Law as Justice in Social and Legal Context - Yenny Febrianty; Fauzan Azima Faturachman; Maudy Anjani; Asmida Ahmad; Viorizza Suciani Putri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Indigenous societies' social interactions are governed by customary law, which has a major impact on cultural identity. Conflicts between local customs and the standardized elements of positive law make it difficult to integrate customary marriage rules into Indonesia's national legal system. Indonesia acknowledges the importance of customary law, yet there is still inconsistency when it comes to marital customs and other areas where it is included in national laws. The goals of this research are twofold: first, to understand how positive law in Indonesia interacts with customary marital law, and second, to find ways to bring these two systems together in a way that promotes inclusivity, justice, and cultural diversity. This study utilizes a normative juridical method by conducting qualitative and comparative analyses of pertinent literature, legal concepts, and legislation. The article looks at marriage legislation from both a positive and traditional perspective, comparing and contrasting the two. In particular, the results show that there are substantial obstacles to bringing traditional marriage regulations into line with modern legal norms in the areas of marriage registration, gender equality, and the age of consent. The research suggests a mechanism for incorporating Indonesia's traditional marriage rules into the country's formal legal framework, with the goals of protecting cultural values and promoting social justice and human rights. Insights from this study may help academics, legal professionals, and legislators make national law more welcoming and sensitive to other cultures.